L’invention d’un modèle : l’architecture des « chais » en Gironde au XIXe siècle - Alain Beschi (In Situ)
Bordelais, broadly absent from viticultural agronomic literature during the whole of the first half of the 19th century, established itself from the 1860’s onwards as a “model wine-growing region”, both for its method of wine-making and for its architecture. But with the mechanisation of the cellars at the end of the century, viticultural architecture from then on found its inspiration in other wine-growing regions, notably in Languedoc.